New features of surface plasmon resonance detected by modulation of electromagnetic radiation polarization - Berezhinsky, L.J.; Matyash, I.E.; Rudenko, S.P.; Serdega, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Using a technique based on modulation of electromagnetic radiation
polarization, we studied the features of surface plasmon resonance in gold nanofilms
deposited onto the surface of a totally reflecting prism (fused quartz). The angular
characteristics of the polarization difference of squares of the reflectance coefficient
modules for s- and p-polarized radiation,
∆ρ =|Rs|² − |Rp|² , were measured (at a wavelength
λ = 0.63 µm) for metal films whose thickness varied from 0 up to 120 nm.
Contrary to the results given by the traditional techniques, the characteristics of ∆ρ peak
under the resonance condition. As a result, two nonresonance components were found in
these characteristics. The values and shapes of their angular dependences are determined
by the coefficients of internal reflection from the metal and insulator that depend on the
film thickness. Application of a model with exponential dependence of the refraction and
extinction coefficients on the metal film thickness led to agreement between the results
of calculation from the Fresnel formulas and those obtained experimentally. It was found
that characteristic parameter of the exponential corresponds to the metal film thickness
value of 11±0.5 nm.